Proceedings of the 28th ACM Joint Meeting on European Software Engineering Conference and Symposium on the Foundations of Softw 2020
DOI: 10.1145/3368089.3409681
|View full text |Cite
|
Sign up to set email alerts
|

Biases and differences in code review using medical imaging and eye-tracking: genders, humans, and machines

Abstract: Code review is a critical step in modern software quality assurance, yet it is vulnerable to human biases. Previous studies have clarified the extent of the problem, particularly regarding biases against the authors of code, but no consensus understanding has emerged. Advances in medical imaging are increasingly applied to software engineering, supporting grounded neurobiological explorations of computing activities, including the review, reading, and writing of source code. In this paper, we present the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 107 publications
0
10
0
Order By: Relevance
“…To properly cover a wide range of programming expertise, we were forced to give up on maintaining gender balance at each expertise level. However, several fMRI studies have reported possible gender differences in behavior, cognitive function, and neuroimaging data (David et al, 2018;Huang et al, 2020). The results obtained via this study might be biased by the gender imbalance of the subject population.…”
Section: Limitations Of the Studymentioning
confidence: 55%
“…To properly cover a wide range of programming expertise, we were forced to give up on maintaining gender balance at each expertise level. However, several fMRI studies have reported possible gender differences in behavior, cognitive function, and neuroimaging data (David et al, 2018;Huang et al, 2020). The results obtained via this study might be biased by the gender imbalance of the subject population.…”
Section: Limitations Of the Studymentioning
confidence: 55%
“…Moreover, the authors suggest that women are as productive as their male colleagues in an inclusive OSS project, with some women developers demonstrating more productivity than the average men developers. Even not supporting any inferences about whether men or women are more accurate at code review, results from Huang et al [PS14]'s study indicates women present more reliable activity patterns.…”
Section: Discussionmentioning
confidence: 78%
“…According to the GitHub dataset of six projects evaluated by Paul et al [PS13], women are more likely to write reviews expressing sentiments in the text to another woman than to a man during code reviews. Huang et al [PS14] used medical imaging and eye-tracking to evaluate the visual and cognitive processes and patterns of neural activation followed by reviewers while performing code reviews. Authors found that women spent significantly more time analyzing pull-request messages and author pictures (regardless of their identity) than the code itself when performing code reviews.…”
Section: Types Of Contributions That Women Make In Oss Projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group of studies addresses developers' cognitive biases that might affect code review outcome [20,35,50,54]. Huang et al investigated how cognitive biases relate to code review process in a controlled experiment using medical imaging and eye-tracking.…”
Section: Cognitive Aspects In Code Reviewmentioning
confidence: 99%